Experimental Study on Separated-flow Transition on a High-lift Blade - S. Yang; F. Tian; C. Teng; B. Xu (Journal of Applied Fluid Mechanics)
The increasing loading level for high-lift blades in low-pressure turbines leads to a laminar separation bubble (LSB) formed on the surface, resulting in a greater profile loss. To obtain a detailed understanding of the flow physics, experiments were conducted at various Reynolds numbers (Re) using complementary hot-wire and hot-film anemometers. Two instability regions are confirmed inside/outside the LSB. The external region is due to the inviscid Kelvin–Helmholtz (K–H) instability, while the internal one originates from the reversed- flow even at a low reversal level. The Strouhal number associated with K–H instability remains constant as Re changes. Furthermore, the modal instability primarily in the form of the K–H mechanism and the non-modal instability due to the streamwise streaks induced by the freestream turbulence (FST) are found to coexist. The non-modal instability contains mainly low-frequency fluctuating energy, which impacts the disturbance energy spectrum within the separated shear layer. This reveals that the inflectional velocity profiles amplify the fluctuating energy within both the K–H frequency band and the low-frequency range. The origin of the latter can be traced upstream of the separation. However, inflectional instability remains immanently linked to the inviscid K–H instability, which cannot be bypassed as Re increases even with a thinner LSB.